2022
DOI: 10.3138/jcfs-2021-0081
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Father Involvement on Their Children’s Self-Esteem in the Arab World

Abstract: To understand the role of Arab fathers in raising their children, which remains understudied, this study analyzed different forms of father involvement during childhood and their relationship with children’s self-esteem during adult life. Drawing on a larger study on father involvement, data were collected from 2,170 respondents across ten countries in the Arab world, consisting of questionnaires about their relationships with their fathers and life history interviews focusing on father involvement. Regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The fathers mainly preferred the games that include physical activities before the programme and then they began giving a place for creative, artistic, and exploratory activities in their games with children thanks to the programme. Various studies in the literature show that the father training given within the scope of family involvement contributed to the fathers positively in terms of spending interactive time with their children (Dingus et al, 2022;Pherson & Robinson, 1990) The fathers understood their influences on the existence of their children with the Father Support Programme. As a result of their study, Kocayörük & Sümer (2009) indicated that the father involvement training activities contributed to the father-child relationship positively and made a change in the behaviours towards children, and this shows the similarity in the research outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fathers mainly preferred the games that include physical activities before the programme and then they began giving a place for creative, artistic, and exploratory activities in their games with children thanks to the programme. Various studies in the literature show that the father training given within the scope of family involvement contributed to the fathers positively in terms of spending interactive time with their children (Dingus et al, 2022;Pherson & Robinson, 1990) The fathers understood their influences on the existence of their children with the Father Support Programme. As a result of their study, Kocayörük & Sümer (2009) indicated that the father involvement training activities contributed to the father-child relationship positively and made a change in the behaviours towards children, and this shows the similarity in the research outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…And likewise, the number of studies that examine the father-child relationship in this period is limited. The importance and necessity of attracting fathers to school through school-family activities are shown among the results of the family involvement practices (Baldwin et al, 2019;Dingus et al, 2022;Maselko et al, 2019). Hence, studies also show that there are also many traditional gender views, separating mother and father roles (Sudkämper et al, 2019;Summer et al,2004).…”
Section: Introductionmentioning
confidence: 99%
“…Their responses were Stigmatization, Resistance, Emotional Difficulties, Unstable Relationships, Fear Social and emotional needs were the essential ingredient of mental health, on the other hand, in the process of acculturation, the social and emotional component was lacking in families and groups. To improve mental health in the future, there was a need to develop sensitivity to social and emotional components associated with the trauma of death (Dingus et al, 2022). For this purpose, sustainable social relationships were important for better emotional regulation and to discourage negative components such as stigmatization, emotional and economic exploitation of grieved women.…”
Section: Discussionmentioning
confidence: 99%
“…Daughter father relationship is based on a strong attachment, moreover, in Asian culture, a woman depends on a male figure. The death of an attachment figure is tragic and the intensity of mental health disturbance depends on the relationship and emotional connection with the deceased (Dingus et al, 2022). Additionally, the reaction toward death differs from other cultures, such as death being more communal than personal.…”
Section: Introductionmentioning
confidence: 99%